Dokument muzyczny jako laboratorium sytuacji ekstremalnych. „Miłość” i „Some Kind of Monster” - Bitka, Stanisław (Humaniora. Czasopismo Internetowe, 2025)
The aim of this article is to demonstrate the potential of documentary Cinema in portraying artistic struggles. Stylistically and aesthetically distant from each other, the bands Miłość (a leading group of the Polish yass scene) and Metallica share surprisingly convergent film portraits: Miłość (2010), directed by Filip Dzierżawski, and Some Kind of Monster (2004), directed by Joe Berlinger and Bruce Sinofsky. Metallica, facing internal tensions, turned to a therapist, with the therapy sessions intertwining with the process of creating new material. In turn, Miłość stands on the verge of reactivation at a time when each of its members has developed a distinctly different artistic path – from avant-garde to mainstream. Both films reveal that by presenting internal conflicts through the form of the observational documentary (Bill Nichols), cinematic narration gains greater engagement potential, allowing viewers to connect with these documentaries as if they were following fictional stories.